Uji Efektifitas ekstrak Daun Beluntas (Plucea indica L.) Untuk Kelancaran Pengeluaran ASI Pada Masa Menyusui Tikus Galur Wistar (Rattus Norvegicus) Betina - Fransiskus Aryo Pratomo (PHARMANAJA : PHARMACEUTICAL JOURNAL OF UNAJA, 2024)
This study aimed to evaluate the effectiveness of Pluchea indica (beluntas) leaf extract in promoting breast milk secretion during the lactation period in female Wistar rats (Rattus norvegicus). The experimental research was conducted at Universitas Adiwangsa Jambi using 24 lactating rats, randomly assigned into four groups: a negative control group (distilled water), a positive control group (commercial lactation booster), and two treatment groups receiving Pluchea indica extract at doses of 200 mg/kg BW and 400 mg/kg BW, respectively. The treatment was administered for 14 consecutive days during the lactation period. Parameters observed included the body weight gain of the pups as an indirect indicator of milk production, along with maternal nursing behavior and physiological conditions.The results demonstrated that administration of Pluchea indica extract, particularly at 400 mg/kg BW, significantly increased (p<0.05) pup body weight compared to the negative control group and showed comparable effectiveness to the positive control group. No signs of toxicity or disruption in maternal behavior were observed throughout the study. In conclusion, Pluchea indica leaf extract shows potential as a natural galactagogue agent that effectively enhances milk production, and it may serve as a promising phytopharmaceutical candidate to support maternal lactation health.